Heterologous Expression of Arabidopsis AtARA6 in Soybean Enhances Salt Tolerance - Hong, Zhipeng; Li, Yang; Zhao, Yang; Yang, Mingyu; Zhang, Xiaoming; Teng, Yuhan; Jing, Linjie; Kong, Danxun; Liu, Tongxin; Li, Shuanglin; Meng, Fanli; Wang, Qi; et al. (Frontiers in Genetics, 2022)
Salt damage is an important abiotic stress affecting the agronomic traits of soybean. Soybeans rapidly sense and transmit adverse signals when salt-damaged, inducing a set of response mechanisms to resist salt stress. AtARA6 encodes a small GTPase, which plays an important role in Arabidopsis vesicle transport and salt tolerance. In this study, we transformed the Arabidopsis gene AtARA6 into the cultivated soybean Shen Nong 9 (SN9). To investigate the salt tolerance pathways affected by AtARA6 in soybean, we performed transcriptome sequencing using transgenic soybean and wild-type (SN9) under salt treatment and water treatment. Our results suggest that AtARA6 is involved in the regulation of soybean SNARE complexes in the vesicle transport pathway, which may directly strengthen salt tolerance. The upregulated RNA-related pathways, including RNA metabolic process, RNA biosynthetic process, regulation of transcription, and regulation of gene expression, in addition to the downregulated metabolism-related pathways, including metabolic process, primary metabolic process, cellular metabolic process, and macromolecule metabolic process, may indirectly contribute to the enhanced salt resistance of AtARA6 transgenic soybean. Our results provide basic insights into the function of AtARA6 in soybeans and its role in abiotic stress processes in plants.